(3cJGH aj fbd CehGd GdeSGLO HYVgG Edi HYVs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi CaGV YdjfG CfhGQkG ef eTcGI GdYQaGf , hLYdfG dcGaI GdNdb gOGI Edi GdMb hHYO aEfG fYde GdcGaI eef hba Ydi cJGHfG gPG Cf GdPi jbJVi Hg GdTQY gh GdYed Ydi GdESJUdGM GdeQSd s
(3BNQgG (B:s
(3ajYde Gdabjg eSYhO Hf eMeO GdMhjJ , hjYed HMSHg ai eG YQV dg ai gPG MGdg Je Pdc s
(3HgG fXGe GdJYbjHIs
(3HBNQgG hdGjI ddabjg eSYhO Hf eMeO GdMhjJ ai eG jMJGL Edjg ef GdCehQ GdTQYjI ai CMhGd GdeSGLOs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143s
Keywords: (3Gdabg GdESdGejs